Answer:
(-5 x)/2
Explanation:
Simplify the following:
-6 (x/4 - (2 x)/3 + (5 x)/6)
Put each term in x/4 - (2 x)/3 + (5 x)/6 over the common denominator 12: x/4 - (2 x)/3 + (5 x)/6 = (3 x)/12 - (8 x)/12 + (10 x)/12:
-6(3 x)/12 - (8 x)/12 + (10 x)/12
(3 x)/12 - (8 x)/12 + (10 x)/12 = (3 x - 8 x + 10 x)/12:
-6(3 x - 8 x + 10 x)/12
The gcd of -6 and 12 is 6, so (-6 (3 x - 8 x + 10 x))/12 = ((6 (-1)) (3 x - 8 x + 10 x))/(6×2) = 6/6×(-(3 x - 8 x + 10 x))/2 = (-(3 x - 8 x + 10 x))/2:
(-1 (3 x - 8 x + 10 x))/2
3 x - 8 x + 10 x = 5 x:
Answer: (-5 x)/2